Synthesis and color properties of the TiO2@CoAl2O4 blue pigments with low cobalt content applied in ceramic glaze. Issue 6 (16th January 2018) - He, Xuanmeng; Wang, Fen; Liu, Hui; Niu, Lijun; Wang, Xinzhen
Abstract: The TiO2 @CoAl2 O4 complex blue pigments with low cobalt content were synthesized through calcinations of the precursor obtained from coprecipitating Co 2+ and Al 3+ to form Co‐Al LDHs (layered double hydroxides) on the surface of TiO2 particles. The structure and the properties of the synthesized pigments were characterized by XRD, SEM, TEM, UV‐Vis spectroscopy, XPS, and colorimeter. The precursors of the blue TiO2 @CoAl2 O4 complex pigments were consisted of LDHs shell layer encapsulated TiO2 microsphere. After calcinations at 1100°C, the LDHs shell layer were absolutely transformed to the spinel CoAl2 O4, and the pigments presented a core‐shell structure and uniform sphere morphology (the diameter of microsphere was about 780 nm). The absorption bands at around 547, 584, and 624 nm in the Uv‐Vis absorption spectra of the TiO2 @CoAl2 O4 complex pigments were corresponded to the characteristic absorption bands of the spinel CoAl2 O4, revealed the pigments with a bright blue hue. In addition, as the mass ratio of CoAl2 O4 /TiO2 increased to 0.4, the blue component of the pigments reached to 27.89 and slight color variation with the increase in the CoAl2 O4 content in a range, possessed low cobalt content and exhibited a stabile performance in commercial low‐temperature ceramic glazes. The XGT results showed that the TiO2 @CoAl2 O4 complex pigments with low cobalt content presented bright color in ceramic glaze. Especially, the synthesized pigments reduced the usage and toxicity of cobalt, which were efficiency for economy and environmental protection.